Nicotinic Receptor Activation Excites Distinct Subtypes of Interneurons in the Rat Hippocampus - McQuiston, A. Rory (J Neurosci, 1999)
We examined the function of nicotinic acetylcholine receptors (nAChRs) in interneurons of area CA1 of the rat hippocampus. CA1 interneurons could be classified into three categories based on nicotinic responses. The first class was depolarized by α7 nAChRs, found in all layers of CA1 and as a group, had axonal projections to all neuropil layers of CA1. The second class had both fast α7 and slow non-α7 nAChR depolarizing responses, was localized primarily to the stratum oriens, and had axonal projections to the stratum lacunosum-moleculare. The third group had no nicotinic response. This group was found in or near the stratum pyramidale and had axonal projections almost exclusively within and around this layer. Low concentrations (500 nm) of nicotine desensitized fast and slow nAChR responses. These findings demonstrate that there are distinct subsets of interneurons with regard to nicotinic receptor expression and with predictable morphological properties that suggest potential cellular actions for nicotinic receptor activation in normal CNS function and during nicotine abuse.